Chemical biology tools to study pantetheinases of the vanin family. (11th August 2014) - Schalkwijk, Joost; Jansen, Patrick
Abstract : VNNs (vanins) are pantetheinases that hydrolyse pantetheine to pantothenic acid and cysteamine. Studies with Vnn1 -knockout mice have indicated a role of VNN-1 in inflammation and stress responses. VNN-1 is highly expressed in liver and is under transcriptional control of PPAR (peroxisome-proliferator-activated receptor)-α and nutritional status, suggesting a role in energy metabolism. Recently, the specific substrates and inhibitors of VNNs were obtained as tools to study VNN biology and to investigate whether VNNs are potential drug targets. Oral administration of RR6, a pantothenone with nanomolar anti-VNN potency, completely inhibited plasma VNN activity in rats and showed favourable pharmacokinetics. Prolonged RR6 administration caused alterations of hepatic and plasma lipid concentrations upon fasting. VNN inhibitors were found to protect pantothenamides (pantetheine analogues with antibiotic activity) against breakdown by plasma VNN, thereby preserving their antibiotic activity. Combination of pantothenamides with a VNN inhibitor showed a strong activity against Staphylococcus aureus and Staphylococcus pneumoniae when assayed in the presence of 10% serum. Recent studies have reported plasma stable pantothenamides that were active against the malaria parasite Plasmodium falciparum . We conclude that VNN inhibitors and pantothenate derivatives that target enzymes in the CoA (coenzyme A) biosynthetic pathway may have potential use as novel drugs in infection, inflammation and metabolism.